EXCAVATION OF BUKIT KAPUR AS A TOURIST DESTINATION IN THE PERSPECTIVE OF MAQASID AL SHARI'AH (International Conference on Social and Islamic Studies, 2021)
Hill and mountain excavation for business purposes is currently a trend in several areas, including in Madura. This excavation of course has an impact not only on ecology but also impact on socio-economic life and the health of the surrounding community. The purpose of this paper is to find out how the existence of limestone excavations that are used as tourist destinations in the study of Maqasid al Syariah. Research methods use a qualitative approach. The data was obtained through interviews, and observations and analyzed using Miles and Huberman's analysis techniques. The results of this study show that the excavation of Bukit Kapur is still relevant to maqasid al Syariah even though the excavation of this limestone hill is still found damage to the environment. The large consideration of madharat and Maslahah becomes important in this discussion. This paper will contribute scientific in terms of Maqasid al Syariah and can be used as a reference in the study of hill excavations that are currently being done by many people.